KEMAJUAN DAN KEMUNDURAN DINASTI SAFAWI DI PERSIA - Safitri, Nopira; Amril M (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2025)
Abstract This article discusses the Safavid Dynasty as one of the most influential Islamic dynasties that ruled Persia from 1501 to 1736 CE. It is notable for establishing Twelver Shi'ism as the official state madhhab and played a significant role in Persia's socio-political and religious transformation. The study aims to describe the rise and decline of the Safavid Dynasty by examining internal and external factors that shaped its trajectory. The findings indicate that the dynasty’s golden era occurred under Shah Abbas I, marked by achievements in politics, economy, science, and the arts. However, weak leadership, internal conflicts, moral decay, and external pressures ultimately led to its downfall. This article affirms that the endurance of a dynasty largely depends on moral integrity, leadership capacity, and responsiveness to external challenges. Keywords: Safavid Dynasty, Persia, Shah Abbas, civilizational progress, dynastic collapse.